Celebrity Endorsements and Brand Attitudes Toward Buying Interest - Ayunda Ramadhani; Nurul Insani (International Journal of Social Science and Business, 2023)
In recent years, the influence of celebrities on brand advertising is very promising. Undoubtedly, celebrity endorsements increase a company's brand awareness through endorsements. This study aims to determine the influence of celebrity endorsement and brand attitude on buying interest in adolescents. This study used a quantitative approach. The subjects of this study amounted to 100 students at SMA X Sangatta Utara who were selected by purposive sampling techniques. The data collection methods used were the scale of purchase intent, celebrity endorsements, and brand attitudes. The data analysis technique used is multiple linear regression. The collected data was analyzed with the help of the Statistical Package for Social Science (SPSS) program version 21.0 for windows. The results of this study showed that there was a significant influence between celebrity endorsement and brand attitude towards buying interest (F = 39.0 16; p = 0.000; R2 = 37.5%). There was no significant effect between celebrity endorsements on buying interest (β = 0.070; t = 1.978; p = 0.544). There was a significant influence between brand attitudes toward purchase intent (β = 0.556; t = 4.859; p = 0.000).